An MRI study of age-related white and gray matter volume changes in the rhesus monkey - Wisco, Jonathan J.; Killiany, Ronald J.; Guttmann, Charles R.G.; Warfield, Simon K.; Moss, Mark B.; Rosene, Douglas L. (Neurobiology of aging, 2008)
We applied the automated MRI segmentation technique Template Driven Segmentation (TDS) to dual-echo spin echo (DE SE) images of eight young (5–12 years), six middle-aged (16–19 years) and eight old (24–30 years) rhesus monkeys. We analyzed standardized mean volumes for 18 anatomically defined regions of interest (ROI's) and found an overall decrease from young to old age in the total forebrain (5.01%), forebrain parenchyma (5.24%), forebrain white matter (11.53%), forebrain gray matter (2.08%), caudate nucleus (11.79%) and globus pallidus (18.26%). Corresponding behavioral data for five of the young, five of the middle-aged and seven of the old subjects on the Delayed Non-matching to Sample (DNMS) task, the Delayed-recognition Span Task (DRST) and the Cognitive Impairment Index (CII) were also analyzed. We found that none of the cognitive measures were related to ROI volume changes in our sample size of monkeys.